Does Rhizobial Inoculation Functionality Vary With Host Plant Genotype? A Case Study of Common Bean Phaseolus Vulgaris l. Germplasms Grown by Smallholder Farmers In Eastern Kenya. - Menge, Ephraim M.; Njeru, Ezekiel M.; Maingi, John (Machakos University, 2018)
Rhizobia inoculants are soil bacteria that promote biological nitrogen fixation (BNF). Understanding of rhizobia-host genotype association is a critical step in enhancing legume productivity. Questionnaires were used to identify the common bean varieties grown in Eastern Kenya. The native rhizobia were obtained from the root nodules of MAC 13 and MAC 64 bean varieties, which were used for trapping. Afterwards, a greenhouse bioassay was set up in a complete randomized design with three replications. Four weeks later, beans were sampled and examined for nodule number (NNO), nodule dry weight (NDW), shoot dry weight (SDW), root dry weight (RDW), shoot nitrogen (%N) and phosphorus (P). Results demonstrated that highest and significant (p<0.001) NDW, SDW and shoot %N content were achieved in a mix of native consortium+exotic rhizobia (Biofix), while the highest and significant (p<0.001) P content was realized in a consortium of native rhizobia inoculation. Moreover, there was a significant interaction (p=0.001) between rhizobia and bean varieties with Kabuu recording the highest NDW, SDW, %N and P contents in a mix of native consortium+exotic rhizobia. Gacere recorded the highest NDW and SDW when inoculated with exotic rhizobia. Native rhizobia inoculation recorded the highest shoot %N variability in all bean varieties when compared to exotic and a mixture of native+exotic rhizobia. These results show the mutual preference that exists between rhizobia and bean varieties and the multistrain synergism between native and exotic rhizobia. Further studies should explicate the performance of diverse native rhizobia inoculants used in this study under field conditions. Key words: Biological nitrogen fixation, Rhizobia inoculation, Common bean, Eastern Kenya
Keywords: Rhizobia inoculation; Biological nitrogen fixation